Ex post disclosure and the coordination of investors' adaptive expectations* - O'BRIEN, JOHN R. (Contemporary Accounting Research, 1990)
This paper provides a dynamic analysis of ex post public disclosure in a privately informed stock market economy. Investors cannot observe the underlying laws of motion of the economy, and this precludes them from immediately forming rational expectations. Instead, expectations are formed adaptively, and two positive roles are identified for public disclosure. First, it enables investors to recursively modify their forecast rules each period using their most recent forecast errors. Second, public disclosure via its recursive modification role imposes a common influence over the time path of each investor's expectations, and this can drive the economy as a whole towards attaining a noisy rational expectations equilibrium. Résumé. L'auteur propose une analyse dynamique de la publication ex post dans un marché boursier disposant d'informations privilégiées. Les investisseurs ne peuvent observer les lois sous‐jacentes aux mouvements de l'économie, et il leur est done impossible de formuler immédiatement leurs prévisions rationnelles. Les prévisions s'élaborent plutoCt de façon adaptative, et deux rôles positifs sont attribués à la publication. Premièrement, elle permet aux investisseurs de procéder à l'ajustement récursif de leurs règles prévisionnelles pour chaque période, à partir de leur erreur prévisionnelle la plus récente. Deuxièmement, la publication, grâce à son rôle d'ajustement récursif, exerce une influence uniforme sur l'évolution temporelle des prévisions de chaque investisseur, ce qui peut mener l'économie dans son ensemble vers un équilibre instable de prévisions rationnelles.